Work ability and physical fitness among aging workers: the Finnish Retirement and Aging Study - Suorsa Kristin; Mattila Ville-Mikko; Leskinen Tuija; Heinonen Olli J; Pentti Jaana; Vahtera Jussi; Stenholm Sari (SPRINGER, 2022)
Background With advancing age, physical capacity gradually decreases which may lead to decreased work ability, if the physical work requirements remain the same. Examination of the importance of physical fitness for work ability among aging workers will help to find potential strategies to promote work ability in old age. The aim of this study was to investigate the association between physical fitness and work ability among aging workers.
Methods Aging workers (n = 288, mean age 62.5, 83% women) from the Finnish Retirement and Aging study underwent cardiorespiratory, muscular fitness and functional testing. Work ability was inquired on a scale 0-10 from poor to excellent. Association between physical fitness indicators and work ability was examined using ordinary least squares regression, taking into account age, gender, occupational status, heavy physical work, body mass index and accelerometer-measured daily total physical activity.
Results VO2peak, modified push-up test and maximal walking speed were positively associated with work ability (beta = 0.51, 95% confidence interval (CI) 0.29-0.74, beta = 0.46, 95% CI 0.26-0.66 and beta = 0.23, 95% CI 0.07-0.39, respectively), while chair rise test time was inversely associated with work ability (beta = -0.23, 95% CI -0.39--0.06). No associations were found between hand grip strength or sit-up test and work ability.
Conclusions Cardiorespiratory fitness, upper body strength, and lower extremity function were positively associated with work ability. Good physical fitness may help to maintain work ability among aging workers.